Farnesyltransferase inhibitor R115777 (Zarnestra, Tipifarnib) synergizes with paclitaxel to induce apoptosis and mitotic arrest and to inhibit tumor growth of multiple myeloma cells - Zhu, Kuichun (The American Society of Hematology, 2005)
Despite major advances, multiple myeloma (MM) remains an incurable malignancy. Recently we have found that disease stabilization was achieved in 64% of patients with advanced MM treated with the farnesyltransferase inhibitor R115777 (Zarnestra) in a phase 2 clinical trial. In order to enhance R115777 antitumor activity in MM, we examined the combination of this novel agent with other anticancer drugs in MM cell lines. In this study, R115777 was found to synergize with paclitaxel and docetaxel, but not with other chemotherapy agents, including doxorubicin, 5-fluorouracil, cisplastin, melphalan, mitoxantrone, and dexamethasone. R115777 synergized with paclitaxel to inhibit MM cell proliferation and to induce apoptosis. Synergism in the induction of apoptosis was accompanied by increase in cytochrome c release and caspase-3 activation. Furthermore, flow cytometry analysis also showed that paclitaxel and R115777 synergized to induce G(2)/M cell-cycle arrest. Importantly, synergism was observed in taxane- and R115777-resistant MM cells. In the human severe combined immunodeficient (SCID-hu) bone model of myeloma growth, the ability of paclitaxel to inhibit tumor growth in vivo was enhanced by R115777. Combination of paclitaxel or docetaxel with R115777 in the treatment of MM cells from patients with multiple myeloma was more beneficial than treatment with single agents. Our results provide the basis for combination therapy clinical trials with paclitaxel or docetaxel with R115777 in MM patients. (Blood. 2005;105:4759-4766)